Serious board games for enhancing socioemotional skills and their impact on motivation in university students - Villena Martínez, Elisa Isabel; Rienda Gómez, Juan José; Sutil Martín, Dolores Lucía; García Muiña, Fernando Enrique (Journal of Management and Business Education, 2023)
The purpose of this research article is to provide evidence on whether training certain social-emotional skills through serious board games has positive effects on students' motivation to successfully complete their university education. Currently, students receive university training in content and skills that, at times, is far from what is demanded by organizations. This desynchrony produces a demotivation effect on students. In the era of Artificial Intelligence, soft skills will be the new hard skills that individuals must have acquired to complete their training and be able to integrate into the labor market effectively. Therefore, it seems necessary and essential to train students' ability to carry out a certain activity, but it is also necessary for them to possess transversal competencies, called soft skills. According to some research, the improvement in the competence of soft skills has direct and positive effects on the motivation, understood as personal entrepreneurship, of students. With this objective, research has been carried out with the students of the Rey Juan Carlos University to evaluate the levels of these skills, their subsequent training through serious board games, and their reevaluation to assess the effect and improvement in their motivation and learning strategies. Given that some soft skills are transferable, teachable, and not assumable by AI, a multistage sample has been carried out on a group of Marketing students constituting a representative sample of 71 individuals. Everyone has answered questionnaires validated by the scientific community in Psychology before and after the training on their motivation and learning strategies, along with other questionnaires, also validated, to measure the levels of socio-emotional soft skills such as empathy, self-concept, and compassion. The results indicate that some of the levels of these skills, along with motivation, are different according to the gender of the individuals; In addition, the determinants of students' pre-training motivation skills are different from the significant post-training factors, the latter being more intrinsically related to the self-awareness, attitude, and self-awareness of the individual and his or her environment.